The Design and Testing of a Special Drinker for Meat Ducks Based on Reverse Engineering - Tao Sun; Huixin Wang; Enze Duan; Gang Ma; Zongchun Bai (AgriEngineering)
Background: Intensive poultry production requires highly efficient drinking systems to ensure both animal welfare and production performance; however, conventional drinkers for meat ducks often suffer from design deficiencies that compromise drinking efficiency and result in significant water wastage. Objectives: To address the drinking water demands in intensive waterfowl farming systems, a specialized drinking device tailored for meat ducks was developed. Methods: The drinking habits of meat ducks were analyzed and the performance of the existing drinkers was evaluated. The deficiencies of the current drinkers were observed and identified by high-speed video, and the parameters of the head of the meat duck were obtained by reverse-engineering technology. Based on this analysis, a specialized drinker for meat ducks was designed, and its performance was confirmed through farming trials. Results: The static and dynamic flow rate tests showed that the output of the new drinker was consistent with the nipple drinker. When the valve rod was pushed upward, the new drinker did not output, which met the design requirements. The results indicated that, under a water pressure of 2.5 kPa, the water loss rate for the designed drinker was 27.4%, which was 15.3% lower than the loss rate of 42.7% observed with the traditional nipple drinker. Conclusion: This study develops a specialized drinker for meat ducks in intensive farming, by utilizing the biting drinking method and incorporating the three-dimensional characteristics of the heads of meat ducks, significantly increasing the effective drinking rate and reducing leakage during the drinking process.